Spatial behavior of plant attributes and losses in the mechanized harvest of common bean (Phaseolus vulgaris L.) - Rafaeli Neto, Sílvio Luís; Pizzol, Flávio João Dal; Debastiani, Paulo Henrique; Agostineto, Mauricio Crestani (Revista de Ciências Agroveterinárias, 2008)
The mechanized harvest of common bean is a growing practice in the farming systems of Santa Catarina State, especially due to the reduction of production costs. However, this advantage has been mitigated for the losses in the process. Harvest losses have been blamed as one of the causes for the crop low productivity in Brazil. One way to minimize such damages is to improve the knowledge about the behavior of theses losses inside a production site and to identity their existing relations with plant and soil attributes, so that growers can act on management practices and machine regulation. This work aimed to analyze variable related to the losses in the mechanized common bean harvest and to evaluate the spatial relations between land altitude, plant height, first legume insertion height, weed natural incidence, grain yield, natural harvest losses, harvest losses in the cut platform and total losses. The total average loss was 14%, with 2% losses due to natural causes, 6% due to the machine internal mechanisms and 6% due to the platform cut. The coefficients of variation were high for almost all variables. There were strong spatial dependences among variables, with the entire reaches being higher than the inter-sample distance. Places with higher altitude had greater grain yield, higher loss on the platform cut, lower natural loss and lower loss in the internal mechanisms. The main causes for losses due to internal mechanisms were the presence of weeds and wet grains at the track.